2011
DOI: 10.1159/000335768
|View full text |Cite
|
Sign up to set email alerts
|

Chloride-led Disruption of the Intestinal Mucous Layer Impedes <i>Salmonella</i> Invasion: Evidence for an ‘Enteric Tear’ Mechanism

Abstract: Background/Aims: Methods: The intestinal epithelial layer can switch from a net absorptive state to one of net secretion in the presence of luminal toxins and pathogens. This suggests an innate defence role for regulated secretion of mucus, electrolytes and water. We hypothesised that chloride-led fluid secretion across the mucus-covered intestinal epithelium alters barrier properties by influencing the overlying mucous-gel layer. Results: We demonstrated that chloride-led disruption of the epithelial-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…FD-4 concentration was calculated from fluorescent standard curves (Spectramax m5e, Molecular Devices, USA). The velocity of FD-4 across the intestinal barrier; the apparent permeability (P app ) for FD-4, was calculated from the following equation: Pappfalse(cm/sfalse)=false(dQ/dtfalse)/false(A·Cofalse), where dQ/dt is the transport rate (mol/s of FD-4), A is the surface area of the monolayer or sac (cm 2 ), and Co is the initial concentration in the donor compartment (mol/mL) 42, 44, 45 .…”
Section: Methodsmentioning
confidence: 99%
“…FD-4 concentration was calculated from fluorescent standard curves (Spectramax m5e, Molecular Devices, USA). The velocity of FD-4 across the intestinal barrier; the apparent permeability (P app ) for FD-4, was calculated from the following equation: Pappfalse(cm/sfalse)=false(dQ/dtfalse)/false(A·Cofalse), where dQ/dt is the transport rate (mol/s of FD-4), A is the surface area of the monolayer or sac (cm 2 ), and Co is the initial concentration in the donor compartment (mol/mL) 42, 44, 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies have implicated a role for NLRP6 in regulating mucus secretion from goblet cells. Nlrp6 −/− mice display altered mucus secretion and increased colonisation of Citrobacter rodentium (Wlodarska et al, ), indicating an inability to clear pathogens (Keely et al, ). In a separate study, goblet cell secretion of MUC2, the main mucin in the intestine, was shown to be NLRP6‐dependent (Birchenough, Nyström, Johansson, & Hansson, ).…”
Section: Inflammasome‐driven Mucus Regulationmentioning
confidence: 99%
“…Studies have implicated a role for NLRP6 in regulating mucus secretion from goblet cells. Nlrp6 −/− mice display altered mucus secretion and increased colonisation of Citrobacter rodentium (Wlodarska et al, 2014), indicating an inability to clear pathogens (Keely et al, 2011).…”
Section: Inflammasome-driven Mucus Regulationmentioning
confidence: 99%
“…Chloride secretion induced in fully differentiated, mucin-secreting HT29-MTX cells results in the shedding of the mucus gel covering the apical cell domain and a reduction in mucus gel density and barrier properties, which in turn limits the innate defense mechanism against S. Typhimurium invasion (749).…”
Section: Host Cellular Defense Responsesmentioning
confidence: 99%